Exercise intervention and sexual function in advanced prostate cancer: a randomised controlled trial. Issue 1 (16th December 2020) - Galvão, Daniel A; Taaffe, Dennis R; Chambers, Suzanne K; Fairman, Ciaran M; Spry, Nigel; Joseph, David; Newton, Robert U
Abstract : Objectives: Treatments for prostate cancer such as androgen deprivation therapy (ADT), surgery and radiation therapy can adversely affect sexual, urinary and bowel function. Preliminary research has demonstrated the efficacy of exercise to preserve sexual function in men with localised prostate cancer receiving ADT, though this has yet to be investigated in a metastatic setting. We examined the effects of a 12-week exercise programme comprising resistance, aerobic and flexibility training on sexual health and function in men with advanced prostate cancer. Methods: Patients with prostate cancer (70.0±8.4 year; body mass index 28.7±4.0 kg/m 2 ) with bone metastases (rib/thoracic spine, 66.7%; lumbar spine, 43.9%; pelvis, 75.4%; femur, 40.4%; humerus, 24.6%; other sites, 70.2%) were randomly assigned to supervised exercise 3 days/week (n=28) or usual care (n=29). Sexual health and function were assessed using the International Index of Erectile Function, the Expanded Prostate Cancer Index Composite and the EORTC-PR25 at baseline and 12 weeks. Results: Patients attended 89% of planned sessions and there were no adverse events. After adjusting for baseline values, there was no significant difference between groups for any measure of sexual function and activity (p>0.05). Additionally, there was no significant difference between groups for urinary and bowel function assessed by the EORTC-PR25 (p>0.05). Conclusions: A short-term programme of supervised exercise does not appear to enhance indices of sexual health and function in men with advanced prostate cancer. Limitations of the intervention included the conservative modular exercise programme, which deliberately avoided loading bone metastatic sites. Trial registration number: ACTRN12611001158954.